“Depressed and Marginalized Voices in Arundhati Roy and Mulak Raj Anand’s Works- a Critical Review” (London Journal of Research In Humanities and Social Sciences, 2023)
Dalits are treated as the worst as they are not. They have to misinterpret in the world of a so called sophisticated society of India by the upper caste ones. They have been called a slice of sordid reality which symbolizes the sufferings stigma in which the Dalits are doomed to live as the result of the present ideological assumptions about caste which has been very so deeply ingrained in the Indian mind that one has wrestled with oneself to feel free from the change of this thousand years old rotten system. Through this paper I want to lay down some of my points that have been expressed in Mulk Raj Anand’s novels Untouchable, Coolie and Arundhati Roy’s The God of Small Things where both of the authors have presented Dalit’s sufferings, struggle and exploitation. The God of Small Things presents an ill-condition of a poor male who is tormented by the ill system of the upper caste people for his crime of love affair with an upper caste girl. In Untouchable, Bakha, a young sweeper from the outcastes’ colony of a north Indian cantonment town bears daily torments like a missionary tries to persuade him to embrace Christianity, he listens to Gandhiji, who advocates social reform and so on. There is a quest in life of Bakha where thinking of everything he had heard, though he could not understand it all. In fact Untouchable is a contrast between rural and urban India and race-relations. Coolie is a pathetic odyssey of Munoo who suffers a lot during his life in the hands of the upper caste and even by his relatives. Life seems to him a very struggled and hard to live in this wretched and bad condition of the so called highly generated world of peoples who consider themselves as the people of the supreme power or the world of oppressor. Munoo is an orphaned village boy who sets out in quest of a livelihood but he is treated as an animal in all spheres of the society. He has to work as a domestic servant, factory worker, a rickshaw-puller which earns him consumption and untimely death because of sufferings and exploitation by the upper caste peoples. Here in today’s so called modern India, the status of the Dalits is not as good as we dream living in the age of technology and information.
Keywords: bakha; caste; dalit; munoo; rural india and urban india; untouchable